Analysis of geothermal impact on metabolite compounds of heat-tolerant plant species using clustering and similarity cliff - N.B. Maulydia; K. Khairan; T.E. Tallei; F. Mohd Fauzi; R. Idroes (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Geothermal zones, famous for their extreme temperatures and exceptional environmental features, offer captivating locations for exploring. These areas are also known to harbor a variety of medicinal plants, historically used for therapeutic properties. Nevertheless, there is a scarcity of information concerning the precise chemical compounds present in plants originating from geothermal regions, especially in relation to their diversity and potential medicinal uses. This study aims to fill this gap by clustering and analyzing the similarity of samples from medicinal plants in three geothermal areas in Aceh Province, Indonesia.METHODS: The collection of medicinal plants was conducted in three geothermal regions within Aceh Province, Indonesia, specifically Ie-Brôuk, Ie-Jue, and Ie-Seu’um. Gas chromatography-mass spectroscopy were conducted to determine chemical compounds from medicinal plants. Clustering analysis and similarity cliff were assessed by employing the simplified molecular input line-entry system and fragment-based fingerprint.FINDINGS: Fifteen different plant species from diverse families—Apocynaceae, Asteraceae, Euphorbiaceae, Fabaceae, Lamiaceae, Moraceae, Pteridaceae, Rhamnaceae, and Verbenaceae were found in this study. A total of 343 chemical compounds were discovered in medicinal plants from the geothermal areas through the use of gas chromatography-mass spectroscopy, indicating a significant diversity. Hexadecanoic acid, methyl ester found in each plant of samples as indiciated as core in flower plot. Clustering analysis identified 98 distinct clusters across the three geothermal areas, with a significant concentration of compounds in the fatty acid group, particularly in cluster 2. The analysis of flexophore similarity revealed 23 neighbor counts, signifying a significant abundance of fatty acids as a predominant. These findings suggest that the chemical compositions of plants in geothermal regions are influenced by the unique environmental conditions, leading to distinct chemical fingerprints for each area.CONCLUSION: This study illustrates that medicinal plants found in geothermal regions contain a broad range of chemical compounds, showcasing a notable diversity in their chemical compositions. The comparison of three geothermal areas in Aceh Province showed that each area has unique characteristics based on the chemical properties of the plants. The findings contribute to a better understanding of the chemical diversity in geothermal regions and emphasize the possibility of uncovering new medicinal compounds. Subsequent studies should increase the sample size and investigate the functional implications of these compounds to maximize their medicinal benefits.